Feasibility insights into the application of Paenibacillus pabuli E1 in animal feed to eliminate non-starch polysaccharides - Li, Gen; Yuan, Yue; Jin, Bowen; Zhang, Zhiqiang; Murtaza, Bilal; Zhao, Hong; Li, Xiaoyu; Wang, Lili; Xu, Yongping (Frontiers in Microbiology, 2023)
The goal of the research was to find alternative protein sources for animal farming that are efficient and cost-effective. The researchers focused on distillers dried grains with solubles(DDGS), a co-product of bioethanol production that is rich in protein but limited in its use as a feed ingredient due to its high non-starch polysaccharides(NSPs) content, particularly for monogastric animals. The analysis of the Paenibacillus pabuli E1 genome revealed the presence of 372 genes related to Carbohydrate-Active enzymes (CAZymes), with 98 of them associated with NSPs degrading enzymes that target cellulose, hemicellulose, and pectin. Additionally, although lignin is not an NSP, two lignin-degrading enzymes were also examined because the presence of lignin alongside NSPs can hinder the catalytic effect of enzymes on NSPs. To confirm the catalytic ability of the degrading enzymes, an in vitro enzyme activity assay was conducted. The results demonstrated that the endoglucanase activity reached 5.37 U/mL, while betaglucosidase activity was 4.60 U/mL. The filter paper experiments did not detect any reducing sugars. The xylanase and beta-xylosidase activities were measured at 11.05 U/mL and 4.16 U/mL, respectively. Furthermore, the pectate lyase and pectin lyase activities were found to be 8.19 U/mL and 2.43 U/mL, respectively. The activities of laccase and MnP were determined as 1.87 U/mL and 4.30 U/mL, respectively. The researchers also investigated the effect of P. pabuli E1 on the degradation of NSPs through the solid-state fermentation of DDGS. After 240 h of fermentation, the results showed degradation rates of 11.86% for hemicellulose, 11.53% for cellulose, and 8.78% for lignin. Moreover, the crude protein (CP) content of DDGS increased from 26.59% to 30.59%. In conclusion, this study demonstrated that P. pabuli E1 possesses various potential NSPs degrading enzymes that can effectively eliminate NSPs in feed. This process improves the quality and availability of the feed, which is important for animal farming as it seeks alternative protein sources to replace traditional nutrients.